Nucleosome positioning and spacing: from genome-wide maps to single arrays. Issue 1 (21st February 2019) - Baldi, Sandro
Abstract : The positioning of nucleosomes relative to DNA and their neighboring nucleosomes represents a fundamental layer of chromatin organization. Changes in nucleosome positioning and spacing affect the accessibility of DNA to regulatory factors and the formation of higher order chromatin structures. Sequencing of mononucleosomal fragments allowed mapping nucleosome positions on a genome-wide level in many organisms. This revealed that successions of evenly spaced and well-positioned nucleosomes—so called phased nucleosome arrays—occur at the 5′ end of many active genes and in the vicinity of transcription factor and other protein binding sites. Phased arrays arise from the interplay of barrier elements on the DNA, which position adjacent nucleosomes, and the nucleosome spacing activity of ATP-dependent chromatin remodelers. A shortcoming of classic mononucleosomal mapping experiments is that they only reveal nucleosome spacing and array regularity at select sites in the genome with well-positioned nucleosomes. However, new technological approaches elucidate nucleosome array structure throughout the genome and with single-cell resolution. In the future, it will be interesting to see whether changes in nucleosome array regularity and spacing contribute to the formation of higher order chromatin structures and the spatial organization of the genome in vivo .